AQUATIC MACROINVERTEBRATE COMMUNITY STRUCTURE IN SOIL USE IN THE LOWER MOCACHE RIVER MICRO-WATERSHED, ECUADOR (Journal of Pharmaceutical Negative Results, 2022)
Aquatic macroinvertebrates are considered an indicator of water quality, along with physicochemical parameters, because these variables have an essential performance in the transformation of organic matter Keywords: ecological quality index, BMWP_Cr, macroinvertebrates, environmental gradient, tropical streams. The research objective was to evaluate the structure of aquatic macroinvertebrate communities in different land uses in the lower micro-watershed of the Mocache River. The D-net method with 500μm mesh was used to collect specimens of soil uses (agricultural, forest and pasture); the Shannon-Weaver diversity, Simpson’s dominance and Pielou indices were applied to evaluate the quality of the water resource. Non-parametric similarity analysis (ANOSIM) and ANOVA variance analysis were used to identify the similarity of aquatic macroinvertebrate genera. To evaluate redundancy (RDA), a physicochemical analysis was performed. The BMWP_Cr index, IHF and QBR were applied to evaluate water quality in soil uses. The abundance of aquatic macroinvertebrate communities showed superficial differences in similarity based on land use, the Brechmorhoga of the order Odonata the most abundant, whose land use is forest cover, categorizing the bioindicator of water quality as “moderately regular.” The order Ephemeroptera presented a greater richness of specimens in agricultural land use, pasture and forest. The physicochemical parameters pH, temperature (°C), dissolved oxygen (DO) and turbidity (NTU) are the most representative of agricultural land use and pastures due to local anthropic pressure. The IHF and QBR indices for land use in forest quality were “Good,” in contrast to agricultural land use and pasture which had quality values of “Moderate” and “Poor.” This indicates that human actions directly impact aquatic ecosystems, modifying land use’s ecological attributes. The BMWP_Cr index showed that the forest land use had excellent water quality.